2022
DOI: 10.3390/vaccines10101749
|View full text |Cite
|
Sign up to set email alerts
|

Social Environmental Predictors of COVID-19 Vaccine Hesitancy in India: A Population-Based Survey

Abstract: Background: During the ongoing COVID-19 pandemic, trust within a community in the projected schemes or strategies to combat COVID-19 depends on the confidence generated and launched by the government and medical employees toward the public. The “vaccination intention” within a community is determined by a range of factors, which include sociodemographic features, personal beliefs, and attitude toward vaccination. Methods: A nationwide survey was conducted involving 2000 people using a Tencent questionnaire pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…Therefore, as some previous studies have suggested, we should improve the accessibility and convenience of parents to accurate and easily accessible information about the COVID-19 vaccine, and increase the dissemination of information related to COVID-19 (41)(42)(43). As reported in previous articles, government and medical workers are trusted sources of information for people with the COVID-19 vaccine (16). Thus, consistent with previous research recommendations, the government cooperating with vaccine development companies and health care workers, should disclose more openly and transparently information about vaccine research, development processes, vaccine safety testing, and disseminate other accurate and reliable information about the COVID-19 vaccine to reduce parental concerns about the safety and efficacy of the COVID-19 vaccine (41,44).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Therefore, as some previous studies have suggested, we should improve the accessibility and convenience of parents to accurate and easily accessible information about the COVID-19 vaccine, and increase the dissemination of information related to COVID-19 (41)(42)(43). As reported in previous articles, government and medical workers are trusted sources of information for people with the COVID-19 vaccine (16). Thus, consistent with previous research recommendations, the government cooperating with vaccine development companies and health care workers, should disclose more openly and transparently information about vaccine research, development processes, vaccine safety testing, and disseminate other accurate and reliable information about the COVID-19 vaccine to reduce parental concerns about the safety and efficacy of the COVID-19 vaccine (41,44).…”
Section: Discussionmentioning
confidence: 91%
“…Among several kinds of official or unofficial information sources, including medical advice, personal beliefs, web/social media, and television, one study ( 19 ) suggested that COVID-19 vaccination triggered intensive responses on social media among Chinese parents, as approximately 70% of the participants were sometimes or always exposed to information specific to COVID-19 vaccination on different social media platforms. Although some studies have suggested that interpersonal communication and the dissemination of information on social media exacerbate people's trust in false information, one study demonstrated that unofficial sources are indispensable health information publishers and disseminators during the current pandemic which will help people to increase the trust in the social environment, including trust in the government and medical personnel, and the vaccine, which played an important role in influencing people's conduct in terms of health protection from the perspective of the prevention and control of COVID-19 ( 16 ). Thus, social media need to be a powerful instrument to distribute the accuracy and objectivity of information and suggestions on the COVID-19 epidemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media may have a positive effect on health literacy behavior. Netizens have the highest trust in national media network platforms and local government websites [ 28 ]. The government should enhance the power and influence of information dissemination in knowledge popularization, news reporting, and information dissemination, carry out social education, and implement COVID-19 prevention and safety measures [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the role of media/social media has also been investigated: Vaccine hesitant/resistant respondents from the United Kingdom were found to consume more information about the COVID-19 pandemic from social media, but less information from newspapers, television, and radio ( 17 ). Overall, social environment factors play an important role in vaccine intention as well as perception of the pandemic ( 18 ).…”
Section: Introductionmentioning
confidence: 99%